Effect of refrigerated storage on betacyanin composition, antibacterial activity of red pitahaya (Hylocereus polyrhizus) and cytotoxicity evaluation of betacyanin rich extract on normal human cell lines - Yong, Y.; Dykes, Gary; Lee, S.; Choo, W. (Elsevier, 2018)
© 2018 Elsevier Ltd Red pitahaya fruit is rich in purplish-red color water-soluble betacyanins. The effect of refrigerated storage at 4 °C on the betacyanin composition of red pitahaya was monitored each day, for one week, using HPLC. The betacyanin content of red pitahaya had increased by 57.2% after storage for six days at 4 °C. From day 2 to day 7, the phyllocactin content decreased from 45.4 ± 1.5% to 38.3 ± 3.1%, whereas the betanin content increased from 37.9 ± 1.6% to 42.7 ± 1.5%. Antimicrobial activity was determined using the broth microdilution assay and expressed as minimum inhibitory concentration (MIC). As compared to the freshly harvested fruits (MIC values: 50,000– > 50,000 µg mL -1 ), fruits that were stored for six days at 4 °C demonstrated better antimicrobial activity (MIC values: 3130–6250 µg mL -1 ) against 10 pathogenic Gram-positive and 6 Gram-negative bacteria. Betacyanin rich extract was also examined against normal human cell lines (HEK-293 and THP-1) and found to be not cytotoxic at the levels of 0.39–3.13 mg mL -1 . In summary, refrigerated storage for 6 days increased the betacyanin content, changed the betacyanin composition in red pitahaya and contributed to higher antimicrobial activity.